The Influence of Social Media Marketing and Online Customer Reviews on Buying Interest in TikTok Market Place: Study in Porli Hamlet, Batang Serangan District, Lalat Regency - Tarigan, Nika Elisa Br; Herlina, Sri (Journal of Management Sains (JMS), 2025)
This research aims to determine the influence of Social Media Marketing and Online Customer Reviews on Purchase Interest at the Tiktok Market Place (Study in Porli Hamlet, Batang Panggang District, Langkat Regency. This research uses 3 (three) variables, namely, social media marketing and online customer reviews as variables free and purchase intention as the dependent variable. The research design used is quantitative research using multiple linear regression analysis techniques with the help of IBM SPSS version 25.0. The data processing results show that social media marketing variables have a positive and significant effect on purchasing interest. This is shown by the t_(calculated) value of the social media marketing variable which is 3.038. Value t_(count)(3.038) > t_table (1.68385). Then the online customer review variable positively and significantly affects purchasing interest. This is shown by the t_(count) value of the online customer review variable which is 4.762. Value t_(count)(4.762) > t_table (1.68385). Apart from that, social media marketing variables and online customer reviews simultaneously have a positive effect on purchasing interest. This is indicated by the Fcount value of 72.638 which is much greater than Ftable 4.07 and the significance value is 0.00 <0.05, so the hypothesis is accepted.